Evaluation of Pregnant Woman Diagnosed With Covid 19 Infection According to Roy Adaptation Model: A Case Report - GÜRLER, Meryem; ARIÖZ DÜZGÜN, Ayten; KAPLAN, Sena; ŞAHİN, Sevil (GEVHER NESIBE JOURNAL OF MEDICAL AND HEALTH SCIENCES, 2023)
Background: Theories and models that form the basis of the nursing profession enable the data collected on the patient to be grouped and interpreted. Sister Callista Roy- Adaptation Model also offers a patient-centered and care result-oriented approach in nursing. It is reported that COVID-19 infection, which is shown as a pandemic in the world, may cause bad consequences on pregnant women. In the study, it was planned to determine the needs of the pregnant woman diagnosed with Covid-19 infection and to manage the nursing process according to RAM. Results: The pregnant woman is 32 years old and was diagnosed with Covid 19 infection in the 32nd week of her second pregnancy. Roy adaptation model was used in order to evaluate the pregnant woman with a systematic and holistic nursing approach during the care process and to increase the harmony of the pregnant woman with her own autonomy at home. The data obtained by obtaining permission from the patient were evaluated, nursing diagnoses were made in the fields of physiological, self and role function, and necessary nursing intervention approaches were made. Conclussion: In the study, a holistic and systematic management of the symptoms of the case was provided in the nursing approach based on The Roy Adaptation model of the pregnant woman who was diagnosed with Covid 19 infection.